Functional differential equations involving the ψ-Caputo fractional derivative - Almeida, Ricardo (2020)
This paper is devoted to the study of existence and uniqueness of solutions for fractional functional differential equations, whose derivative operator depends on an arbitrary function. The introduction of such function allows generalization of some known results, and others can be also obtained.